Low Dark Current and Performance Enhanced Perovskite Photodetector by Graphene Oxide as an Interfacial Layer - Hassan, Ali; Azam, Muhammad; Ahn, Yeong Hwan; Zubair, Muhammad; Cao, Yu; Khan, Abbas Ahmad (Nanomaterials, 2022)
Organic–inorganic hybrid perovskite photodetectors are gaining much interest recently for their high performance in photodetection, due to excellent light absorption, low cost, and ease of fabrication. Lower defect density and large grain size are always favorable for efficient and stable devices. Herein, we applied the interface engineering technique for hybrid trilayer (TiO2/graphene oxide/perovskite) photodetector to attain better crystallinity and defect passivation. The graphene oxide (GO) sandwich layer has been introduced in the perovskite photodetector for improved crystallization, better charge extraction, low dark current, and enhanced carrier lifetime. Moreover, the trilayer photodetector exhibits improved device performance with a high on/off ratio of 1.3 × 104, high responsivity of 3.38 AW−1, and low dark current of 1.55 × 10−11 A. The insertion of the GO layer also suppressed the perovskite degradation process and consequently improved the device stability. The current study focuses on the significance of interface engineering to boost device performance by improving interfacial defect passivation and better carrier transport.
Keywords: Defect passivation; Graphene oxide; Low dark current; Perovskite; Photodetector